STRENGTH, FLEXIBILITY AND SPASTICITY OF KNEE EXTENSORS IN MUSCLE-BUILDING PRACTITIONERS - Matias, Amanda Gilvani Cordeiro (2017)
Introduction: Exercises of strength, flexibility and resistance, compiled in the practice of muscle-building, have the purpose of maintaining and improving the physical conditioning and also the corporal aesthetics. Objective: To evaluate the relationship of strength and flexibility of knee extensors in women practicing muscle-building. Materials and methods: This is a cross-sectional analytical study carried out at a gym in Vitória da Conquista, Bahia. A sociodemographic questionnaire was used, with pre-structured questions about the study theme. The 1-RM strength test was applied as the participants of the study was in the leg extension, the femoral quadriceps flexibility was measured through the fleximeter and the Ely test was applied. Results: 30 women aged 20-35 years participated in the study, 50% of which were students. Positive but not significant correlation was found between femoral quadriceps strength and flexibility in the evaluated group. The evaluation of femoral rectus spasticity as measured by the Ely test was positive in (20) 66.67% of the women, and 70% of them reported not performing femoral quadriceps stretching. Conclusion: Spasticity of the femoral rectus indicates a possible relation with the absence of pre-training quadriceps stretching. However, there was no significant correlation between strength and flexibility of knee extensors in muscle-building practitioners in this sample. Muscle-building alone did not show significant flexibility and femoral quadriceps strength in the evaluated women.